Infosys : phases in corporate entrepreneurship - Thomas, Nobin (London : SAGE Publications: SAGE Business Cases Originals, 2021)
Infosys grew from a startup with a budget of USD 250 to a global leader with presence in 46 countries, USD 12.7 billion total revenue and more than 200,000 employees. Infosys was pivotal in establishing India as a major software hub. After appointing the first non-founder CEO, Sikka, tension arose between the founders and the CEO, who had the support of the board. At the center of the contention was the acquisition of a company called Panaya in 2015. An anonymous whistle-blower complaint claimed that the acquisition was overvalued. Narayana Murthy, founder and former CEO, questioned the Panaya deal and other issues like severance payouts for some of its employees. Murthy stated that the responsibility of Infosys was to shareholders, while ensuring transparency and accountability to every one of the stakeholders.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Infosys Foundation (India); Corporations -- Growth; Corporations -- Investor relations; Business ethics